PENGARUH PENGANGGARAN PARTISIPATIF, JOB RELEVANT INFORMATION DAN ASIMETRI INFORMASI PADA BUDGETARY SLACK DIMODERASI KARAKTER PERSONAL - Dewi, Putu Nadya Pradnyani; Yenni Latrini, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Budgets are often the only measure of an organization's compliance with applicable regulations. Not infrequently, many deviations are found just by looking at the difference between the realization and the budget that has been set. The government's performance appraisal is based on whether or not the budget target has been achieved. This will encourage subordinates to create budget slack or slack. Agents create slack by estimating lower revenues and overestimating costs, or by overestimating the inputs required to obtain a unit of output. This study aims to examine the effect of participatory budgeting, job relevant information, and information asymmetry on budgetary slack with personal character as moderating variable. The population and sample in this study were 69 members of the OPD Karangasem Regency. The results of this study indicate that participatory budgeting, job relevant information, and information asymmetry have a significant effect on budgetary slack. However, this study also found that personal character failed to moderate the effect of each hypothesis. This research has implications for the authorities as determinants of further steps and policies related to budget planning.